2013 Lush Science Prize. Issue 6 (December 2014) - Harrison, Rob
The annual Lush Science Prize is designed to reward outstanding contributions to 21st Century Toxicology Research. A Background Paper is prepared each year prior to the judging process, in order to provide the judging panel with a brief overview of current developments in the field of Replacement alternatives, particularly those relevant to the concept of toxicity pathways. The Background Paper includes information on some key institutional developments in the area — such as the OECD's Adverse Outcome Pathway Project, the Hamner Institute's work, and the Human Toxome Project, and on the phenomenon of collaborative computer systems relevant to the field. From the literature review that was also performed as part of the background research, the two papers receiving the highest score were recommended for consideration by the judges for the 2013 Science Prize.